Comparing core-genome MLST with PFGE and MLST for cluster analysis of carbapenem-resistant Acinetobacter baumannii - Tingting Li; Yunxing Yang; Rushuang Yan; Peng Lan; Haiyang Liu; Ying Fu; Xiaoting Hua; Yan Jiang; Zhihui Zhou; Yunsong Yu (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: Carbapenem-resistant Acinetobacter baumannii (CRAB) is a prevalent pathogen contributing to hospital infections. Pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST) and core-genome MLST (cgMLST) are frequently used methods to illuminate the nosocomial transmission of CRAB. In this study, we compared the discriminatory power of the three typing methods. Methods: Antimicrobial susceptibility tests were performed by the broth microdilution and Vitek2 methods. PFGE, MLST and cgMLST were conducted to determine the clonality and phylogenetic relationship of the strains. Whole-genome sequence data were acquired by an Illumina HiSeq 2000, and cgMLST was analysed by the Ridom SeqSphere+ v.7.2.3 software. Results: A total of 149 carbapenem-resistant A. baumannii isolates had 15 different PFGE profiles (A-O type), and 73 of the isolates had related subtypes (A1 and A2), accounting for the majority of type A isolates. The maximum-likelihood phylogenetic analysis based on the cgMLST genes grouped the same PFGE clonal pattern A into nine different clusters. ST_Pasteur grouped all the strains into ST2, whereas ST_Oxford grouped the PFGE clonal pattern A isolates into six STs. In addition, the gdhB allele in the ST_Oxford scheme had two copies in five strains, which complicated the ST_Oxford typing. Conclusions: cgMLST was more discriminant than PFGE and MLST. CgMLST is the most suitable and comprehensive method for genotyping A. baumannii in surveillance and epidemiological research.